GE_GERICHTE P/4888/2018 vom 31. Juli 2023 - GE Cour de justice (2023)
ESCROQUERIE EN MATIÈRE DE PRESTATIONS;PRESCRIPTION;RECEL;PORNOGRAPHIE DURE | CP.146; CP.148a; CP.109; CP.160; CP.172ter; CP.197.al4.par1